Information security practice and experience 7th International Conference, ISPEC 2011, Guangzhou, China, May 30 - June 1, 2011. Proceedings - ISPEC 2011 (2011 Guangzhou, China); Bao, Feng.; Weng, Jian.; SpringerLink (Online service). (Berlin New York Springer, 2011)
This book constitutes the refereed proceedings of the 7th International Conference on Information Security Practice and Experience, ISPEC 2011, held in Guangzhou, China, in May/June 2011. The 26 papers presented together with 6 short papers were carefully reviewed and selected from 108 submissions. They are grouped in sections on public key encryption, cloud security, security applications, post-quantum cryptography and side-channel attack, block ciphers and MACs, signature, secrete sharing and traitor tracing, system security and network security, and security protocols.
Electronic reproduction.
Keywords: Computer security -- Congresses; Data encryption (Computer science) -- Congresses; Data protection -- Congresses; Electronic books